Applications of Three-Dimensional LBM-LES Combined Model for Pump Intakes (Communications in Computational Physics, 2018)
Lattice Boltzmann model (LBM) in conjunction with an accurate Large EddySimulation (LES) technology was proposed to simulate various vortical structures andtheir evolutions in open pump intakes. The strain rate tensor in the LES model is locallycalculated by means of non-equilibrium moments based on Chapman-Enskogexpansion, and bounce-back scheme was used for non-slip condition on solid wallsand reflection scheme for free surface. The presented model was applied to investigatefree-surface and wall-attached vortices for different water levels and flow rate. Thevortex position, shapes and vorticities were predicted successfully under three flowingcases (i.e. critical water level (CWL), lower water level, lower flow rate), and thenumerical velocity and streamline distribution were analyzed systematically. For CWLbased on Froude number considering open channel flows, the shape and the locationof various dynamic vortices were captured. Compare to the experimental results ofCWL, more vortices were predicted for lower water level, and less vortices were observedfor lower flow rate. The predicted velocities and vortex locations are in goodagreement with the experimental of a small physical model. The comparisons demonstratedthe feasibility and stability of above-mentioned model and numerical methodin predicting vortex flows inside open pump intakes.